IMPLEMENTASI EXTREME PROGRAMMING PADA PERANCANGAN SISTEM INFORMASI PEMBAYARAN IURAN PADA SMK SETIA GAMA BERBASIS WEB - Wahyu Nurdiansyah; Agung Perdananto (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Along with the development of computer technology and information technology, it is time for schools to develop an effective and efficient information system in order to be able to improve the quality of communication with students and parents/guardians of students as well as other school stakeholders. The problem that exists at Setia Gama Vocational School is that the process of processing financial data, especially the process of paying tuition fees, is still manual, causing problems in data processing, financial reports on financing education development, delays in preparing financial reports which take up a lot of time, resulting in ineffective work. In connection with these problems, a web-based information system application is needed in paying tuition fees, where this system will facilitate computerized data processing, in this case, authorization of payment systems for SPP (Educational Development Donations) which can be accessed at any time quickly and efficiently. The SPP payment information system provides accurate and well-documented recording information and the SPP payment information system makes it easier for treasurers to recap financial reports.